PERANCANGAN PENGOLAH LIMBAH CAIR KOMBINASI PROSES KONTAK DAN AEROBIC LAGOON DENGAN MENGGUNAKAN VISUAL BASIC 6 - Subagyo, Heru (Jurnal Rekayasa Lingkungan)
Application of computer programming is cheaper and faster method to design waste water treatment reactor. The aim of the program are to calculate dimension of unit operation of waste water treatment type contact process, aerobic lagoon and sedimentation pond and to count BOD output from waste water treatment and arrange of unit operation. It uses Computer Language Visual Basic 6.Key words: Contact Proses, Aerated Lagoon, dimension, BOD, computer programming